Why Buy Local?. Issue 1 (28th August 2020) - Ferguson, Benjamin; Thompson, Christopher
Abstract: This article critically assesses the moral arguments that speak in favour of three consumer options: buying local food, buying global (non‐local) food, and buying global food while also purchasing carbon offsets to mitigate the environmental impact of food transportation. We argue that because the offsetting option allows one to provide economic benefits to the poorest food workers while also mitigating the environmental impact of food transportation it is morally superior to the alternatives.